Influence of Location and Product Diversity on Consumer Satisfaction - Sri Julfadiati (Almana : Jurnal Manajemen dan Bisnis, 2021)
The location of the Amahami market is located near the highway, to the right of the road before entering the residential community of the city of Bima. . Amahami market is the most extensive and superior traditional market in Bima city compared to other markets, so that all kinds of basic needs of the community are available. In addition to having advantages and uniqueness, the Amahami market also has disadvantages that are not liked and can reduce public interest in buying. The purpose of this study was to determine the effect of location and product diversity either partially or simultaneously on consumer satisfaction in the Amahami Bima market. The population of this research is all consumers who have bought in the Amahami market whose number is unknown and the researcher uses a sample of 100 people. data analysis techniques using multiple regression, t-test, and f test. The results prove that there is a significant influence between the location variable and product diversity on consumer satisfaction at the Amahami market, Bima City, and from the t-test results, that the location variable has a greater influence on consumer satisfaction than the product diversity variable.